Metallo-β-lactamase–producing imipenem-resistant Pseudomonas aeruginosa clinical isolates in a university teaching hospital in Malaysia: detection of IMP-7 and first identification of IMP-4, VIM-2, and VIM-11 - Khosravi, Yalda; Tay, Sun Tee; Vadivelu, Jamuna (Elsevier, 2010)
Ninety (n = 90) imipenem-resistant Pseudomonas aeruginosa (IRPA) clinical isolates collected randomly during 2005 to 2008 from University Malaya Medical Center were assessed for the presence of different variants of metallo-β-lactamase (MBL) genes. Polymerase chain reaction (PCR) assay detected 32 (n = 32) MBL gene PCR-positive isolates with the presence of blaIMP gene in 14 (n = 14) and blaVIM in 18 (n = 18) isolates. Four allelic variants, blaIMP-7 (12 isolates), blaIMP-4 (2 isolates), blaVIM-2 (17 isolates), and blaVIM-11 (1 isolate), of MBL genes were identified. This study is the first report of detection of blaIMP-4, blaVIM-2, and blaVIM-11 MBL genes from IRPA clinical isolates in Malaysia.